Lipid Assemblies as Tools for Drug Delivery - Anju Gupta (International Journal of Lipids, 2020)
This review discusses lipid assemblies—from liposomes to solid lipid nanoparticles—as platforms for drug delivery. It covers design principles, targeting strategies, and manufacturing considerations.
Keywords: Lipid Assemblies